Pharmacological Targeting of BMP6-SMAD Mediated Hepcidin Expression Does Not Improve the Outcome of Systemic Infections With Intra-Or Extracellular Gram-Negative Bacteria in Mice - Hoffmann, Alexander; de Souza, Lara Valente; Seifert, Markus; von Raffay, Laura; Haschka, David; Grubwieser, Philipp; Grander, Manuel; Mitterstiller, Anna-Maria; Nairz, Manfred; Poli, Maura; Weiss, Günter (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction Hepcidin is the systemic master regulator of iron metabolism as it degrades the cellular iron exporter ferroportin. In bacterial infections, hepcidin is upregulated to limit circulating iron for pathogens, thereby increasing iron retention in macrophages. This mechanism withholds iron from extracellular bacteria but could be of disadvantage in infections with intracellular bacteria. We aimed to understand the role of hepcidin in infections with intra- or extracellular bacteria using different hepcidin inhibitors. Methods For the experiments LDN-193189 and oversulfated heparins were used, which interact with the BMP6-SMAD pathway thereby inhibiting hepcidin expression. We infected male C57BL/6N mice with either the intracellular bacterium Salmonella Typhimurium or the extracellular bacterium Escherichia coli and treated these mice with the different hepcidin inhibitors. Results Both inhibitors effectively reduced hepcidin levels in vitro under steady state conditions and upon stimulation with the inflammatory signals interleukin-6 or lipopolysaccharide. The inhibitors also reduced hepcidin levels and increased circulating iron concentration in uninfected mice. However, both compounds failed to decrease liver- and circulating hepcidin levels in infected mice and did not affect ferroportin expression in the spleen or impact on serum iron levels. Accordingly, both BMP-SMAD signaling inhibitors did not influence bacterial numbers in different organs in the course of E.coli or S.Tm sepsis. Conclusion These data indicate that targeting the BMP receptor or the BMP-SMAD pathway is not sufficient to suppress hepcidin expression in the course of infection with both intra- or extracellular bacteria. This suggests that upon pharmacological inhibition of the central SMAD-BMP pathways during infection, other signaling cascades are compensatorily induced to ensure sufficient hepcidin formation and iron restriction to circulating microbes.